Revista Complutense de Historia de América: balance de una política editorial y retos del futuro digital - Arrigo Amadori; Pilar Ponce Leiva (Nuevo mundo - Mundos Nuevos, 2010)
In tune with the thematic content established by the International Congress for which it has been presented, the text offers an assessment of the current situation of the Revista, in terms of its contents, quality control and degree of visibility. The challenges posed for the future lie in the internationalization of the journal, the transparency of its management, the highest quality of content, and the form, which the journal’s electronic edition may adopt in the future.